Pendekatan Problem Posing Berlatar Pembelajaran Kooperatif untuk Topik Sudut - Sudarsono, Sudarsono (Program Studi Pendidikan Matematika, 2024)
to create a learning device with a good cooperative learning background problem posing approach to an angle topic, to explain how effective learning is with this approach to teaching an angle subject, and to find out how the student's learning outcomes by this approach are compared to the students' learning outputs by conventional learning approach. The research is designed as a mixed research and uses instruments such as learning output tests, student activity sheets, learning management sheets and student transportation. Based on the results of inferential statistical analysis, students' learning outcomes for angle topics with an approach to problem posing in the context of cooperative learning are better compared to students' mathematics.